2004
DOI: 10.1016/j.accreview.2004.02.072
|View full text |Cite
|
Sign up to set email alerts
|

A randomized comparison of off-pump and on-pump multivessel coronary-artery bypass surgery

Abstract: A randomized comparison of off-pump and on-pump multivessel coronary-artery bypass surgery. The New England journal of medicine, 350 (1). pp. 21-8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
119
3
12

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(138 citation statements)
references
References 23 publications
4
119
3
12
Order By: Relevance
“…There was a higher overall graft patency rate for the on-pump group, which was entirely due to left internal mammary artery or radial artery grafts. There was no difference in patency rates for vein grafts (95% in the on-pump group and 91% in the off-pump group; P=0.42) (43).…”
Section: Surgical Techniquementioning
confidence: 81%
“…There was a higher overall graft patency rate for the on-pump group, which was entirely due to left internal mammary artery or radial artery grafts. There was no difference in patency rates for vein grafts (95% in the on-pump group and 91% in the off-pump group; P=0.42) (43).…”
Section: Surgical Techniquementioning
confidence: 81%
“…Khan et al [73] reported patency rates of 88% and 98%, respectively, in OPCAB and CABG with bypass surgery. However, a closer analysis of this study [73] shows that the limited experience of the surgeons, coupled with the intraoperative administration of a relatively low dose of heparin, the absence of aggressive postoperative antiplatelet therapy with clopidogrel, and the failure to use new suction devices to optimize exposure, may have confounded the analyses of graft patency among patients who underwent off-pump procedures [74].…”
Section: Length Of Hospital Stay Mortality Rates and Cost Savingsmentioning
confidence: 99%
“…Khan y cols mostraron que a los tres meses de la cirugía, la permeabilidad global de los puentes realizados sin CEC era significativamente menor que la de los puentes realizados con bomba (88% versus 98%) 15 . Hannan y cols estudiaron 13.889 pacientes operados sin CEC con 35.941 pacientes operados con CEC entre los años 2001 y 2004 en el estado de Nueva York.…”
Section: Discussionunclassified